INTERDISCIPLINARY APPROACH TO THE DESIGN OF EVENTS ARCHITECTURE ON THE EXAMPLE OF A MOBILE EXHIBITION PAVILION - Shataliuk, Yuliia; Shataliuk, Denys (SWorld-Ger Conference proceedings, 2023)
The article updates issues of an interdisciplinary approach to the design of events architecture. The peculiarities of work and interaction in interdisciplinary teams are revealed. The role of interdisciplinary teams in increasing users’ engagement and im